2012
DOI: 10.1016/s0377-1237(12)60021-5
|View full text |Cite
|
Sign up to set email alerts
|

Stress fractures—a prospective study amongst recruits

Abstract: BACKGROUNDStress fracture (SF) is the single most common cause for the lost number of manpower days during training of recruits in the Armed Forces. This prospective study was undertaken with a view to develop baseline data on incidence of SF and to identify related variables. METHODA prospective study over a period of five years during [2004][2005][2006][2007][2008][2009] in which a total of 8,570 recruits were enrolled at the start of their training to find out the incidence and pattern of SFs. RESULTSA tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 21 publications
2
21
2
1
Order By: Relevance
“…However, in India two studies by Agrawal PK and Dash N et al, reported high incidence of 11.4% and 7.04% in two different military training centres [4,6]. Apparently, the 15% incidence of SFs in our study far exceeds this figure or those reported from any previous study.…”
Section: Methodscontrasting
confidence: 76%
See 1 more Smart Citation
“…However, in India two studies by Agrawal PK and Dash N et al, reported high incidence of 11.4% and 7.04% in two different military training centres [4,6]. Apparently, the 15% incidence of SFs in our study far exceeds this figure or those reported from any previous study.…”
Section: Methodscontrasting
confidence: 76%
“…An additional bone scan was not performed in cases where radiographs were inconclusive as reported by Agrawal PK in his study [6]. It is thus likely that the incidence, we reported, could have been even higher if a bone scan or an additional scintigraphy was performed.…”
Section: Methodsmentioning
confidence: 73%
“…[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Number of fractures and body site of the fracture were also recorded (Table 3). 19,20,[39][40][41] Bone mineral density values were extracted from the different studies, and only raw data (unadjusted) were used to perform the meta-analyses. Dual-energy X-ray absorptiometry enables different types of scans that give information on several regions.…”
Section: Data Extractionmentioning
confidence: 99%
“…The 20 studies included 37 134 individuals (BMD data were available for 4003 individuals, and fracture rate data were available for 33 131 individuals). 19,20,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] The mean age of the participants varied from 25 to 80 years, and most of the studies equally sampled omnivores and vegetarians/vegans. One study only included men (5%; n ¼ 1/20), most of the studies (65%; n ¼ 13/20) only included women, and 6 studies included both women and men (30%; n ¼ /20).…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation